Into the real - Ringo, John, 1963-; Sherrer, Lydia (Ringo, John, 1963- TransDimensional hunter., 2022)
"Lynn Raven may be the boss master of WarMonger 2050 with her online persona of "Larry the Snake," but when the CEO of Tsunami Entertainment personally asks her, as a favor, to beta test a new augmented reality game, she has to face her greatest fear: Going outside and dealing with, ugh, people. As she becomes more immersed in the game, the stakes rise and so do the obstacles. Strife between teammates, a ruthless rival team, and these strange glitches that make it seem like the game algorithm (or maybe "game AI"?) has it in for her. Now she has to face a new fear: is she willing to step into the real to win the future she's always wanted? What do you do when a game and real life merge?"--